The Phenomenon of Fear of Missing Out (FOMO) in Hangout Activities at Pasaraya Blok M - Nabilla Diandra Prakasa; Adella Dwi Anjani; Zahrina Izzati; Fadillah Dini Rasasti; Maydina Amanatul Latifah (Semantik: Journal of Social, Media, Communication, and Journalism, 2025)
Fear of Missing Out (FOMO) is the fear of feeling "left behind" due to not participating in certain activities. It is a feeling of anxiety and fear that arises within a person due to missing out on something new, such as news, trends, and other things. One cause of FOMO is the use of social media. The development of today's technology makes it easy for us to receive millions of pieces of information. The phenomenon of Fear of Missing Out (FOMO) is one of the important factors influencing the social behavior of the younger generation in the digital media era. This study aims to explain how the habit of 'hanging out' is driven by the FOMO phenomenon as a way to maintain membership in social groups. This study uses a qualitative approach with a descriptive interpretative method within the constructivism paradigm. Data were collected through in-depth interviews with young informants who actively hang out at Pasaraya Blok M, supported by social media observation and documentation. The results show that hanging out is no longer understood merely as a recreational activity or a way to fill free time, but has shifted into a social practice laden with symbolic meaning, especially in the context of identity formation and self-existence. Exposure to social media content, particularly through TikTok and Instagram, shapes the social construct of Blok M as a popular and desirable public space. Based on Maslow and Glasser's perspective, FOMO is understood to be a manifestation of an unstable social need. This study concludes that the hangout culture at Pasaraya Blok M functions not only as a space for social interaction but also as a medium for self-representation, reflecting the dynamic psychological needs of the younger generation within the context of urban digital culture.